2012
DOI: 10.1021/ja211581b
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study on the B–Z Junction Formation of DNA Duplexes Induced by Z-DNA Binding Domain of Human ADAR1

Abstract: Z-DNA is produced in a long genomic DNA by Z-DNA binding proteins, through formation of two B-Z junctions with the extrusion of one base pair from each junction. To answer the question of how Z-DNA binding proteins induce B-Z transitions in CG-rich segments while maintaining the B-conformation of surrounding segments, we investigated the kinetics and thermodynamics of base-pair openings of a 13-bp DNA in complex with the Z-DNA binding protein, Zα(ADAR1). We also studied perturbations in the backbone of Zα(ADAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The previous study reported that the chemical shift of W195-Hε1 side-chain in the Zα ADAR1 -bzDNA13 complex displays the initial contact conformation at P/N ≤ 1.0 but shows Z-DNA bound conformation at P/N = 2.0. 9 Similarly, we observed the severely broadened W195-Hε1 signal displaying the initial contact conformation at P/N ratio = 0.7 ( Fig. 2A).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…The previous study reported that the chemical shift of W195-Hε1 side-chain in the Zα ADAR1 -bzDNA13 complex displays the initial contact conformation at P/N ≤ 1.0 but shows Z-DNA bound conformation at P/N = 2.0. 9 Similarly, we observed the severely broadened W195-Hε1 signal displaying the initial contact conformation at P/N ratio = 0.7 ( Fig. 2A).…”
Section: Resultssupporting
confidence: 70%
“…The previous study found that in the 13-bp bzDNA13, the T−2 and T−3 imino resonances completely disappeared at P/N = 0.9. 9 However, Zα ADAR1 binding did not change the peak intensities in the BBZ-20 when P/N ≤ 2.5 ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations